A trend analysis of the prevalence of opioid misuse, social support, and suicide attempt among American Indian/Alaska native high school students in New Mexico: 2009-2019 Youth Risk Resiliency Survey (YRRS) - Daniel Opoku Agyemang; Erin Fanning Madden; Kevin English; Kamilla L. Venner; Handy Rod; Tejinder Pal Singh; Fares Qeadan (BMC, 2022)
Abstract Background American Indian and Alaska Native (AI/AN) youth face stark inequities in opioid misuse, social support, and suicide attempt. This study examined trends in these behavioral measures among AI/AN students in New Mexico (NM). Methods Using the NM oversampled Youth Resiliency and Risk Survey (NM-YRRS, 2009 - 2019: odd years), prevalence estimates of opioid misuse, social support (SS), and suicide attempt for AI/AN high school students were generated. Trends over time were assessed via linear regression of weighted proportions according to Peter Armitage. Stratified trends by demographics were also employed. Results While the prevalence of suicide attempt did not change significantly over time, it was consistently higher among females (2011-2019), those who misused opioids, received low social support, had a mother with less than high school education, had a C, D, or F for academic performance, and non-straight students relative to their counterparts. In particular, the prevalence of suicide attempt among AI/AN students who reported opioid misuse in 2009 was significantly higher by 25.4% than their counterparts who did not report opioid misuse (35.8% vs. 10.4%.) A significant decreasing trend over time (2009-2017) was observed for opioid misuse (16.1%↓8.8%, p-value = 0.0033), including when stratifying by sex (males: 15.9%↓9%, p-value = 0.002; females: 16.2%↓8.6%, p-value = 0.012). Youth with high maternal education exhibited significant decline in opioid misuse (13.5%↓6.7%, p-value = 0.019; 2011-2017.) Opioid misuse increased significantly from 2017 to 2019 (8.8%↑12.9%, p-value < 0.0001.) For instance, in 2019 among AI/AN students who reported low social support, opioid misuse was roughly doubled (18.9% vs. 8.5%, p < 0.0001), and suicide attempt was tripled (21.3% vs. 7.0%, p < 0.0001) compared to students with high social support. Conclusion No significant trend was observed for suicide attempt. We observed a significant decreasing trend in opioid misuse between 2009 through 2017 but a significant increase from 2017 to 2019. A higher level of maternal education (college or above), and an A or B school grade performance were protective against both opioid misuse and suicide attempt.